The Effect of Short Duration Electric Current on the Quasi-Static Tensile Behavior of Magnesium AZ31 Alloy - Trung Thien Nguyen; Thai Vinh Nguyen; Sung-Tae Hong; Moon-Jo Kim; Heung Nam Han; Fabrice Morestin (Advances in Materials Science and Engineering)
The effect of a single pulse of electric current with short duration on the quasi-static tensile behavior of a magnesium AZ31 alloy is experimentally investigated. A single pulse of electric current with duration less than 1 second is applied to the specimen, while the specimen is being deformed in the plastic region under quasi-static tensile loads. After a nearly instant decrease of flow stress at the pulse of electric current, the flow stress shows strain hardening until the failure of the specimen. The experimental result shows that the strain-hardening parameters (the strength coefficient and the strain-hardening exponent) of the hardening curve after the electric current strongly depend on the applied electric energy density (electric energy per unit volume). Empirical expressions are suggested to describe the hardening behavior after the pulse as a function of the electric energy density and are compared with the empirical expressions suggested for advanced high-strength steels.